Rutinitas Wartawan dalam Memproduksi Berita - Quidora Ledo Soera; Petrus Ana Andung; Monika Wutun (Jurnal Communio : Jurnal Jurusan Ilmu Komunikasi, 2019)
The rapid development of information and communication technology brings relevant changes in several areas of human life. No exception with the field of journalism. Developments that influence the existence of the media force conventional media to provide new policies that are more efficient and effective for society. One of them is by making an online version of the news portal. Increasingly intense media competition requires online journalistic media workers to work fast from searching to working on news that is a routine for journalists. The purpose of this study was to find out the routines of ANTARA News NTT online media reporters in producing news and to find out the meaning of routines by ANTARA News NTT online media reporters in producing news. The theory used in research is the theory of new media / new media. The method in this study uses ethnographic media methods. Data were collected through in-depth interview techniques, participatory observation, and documentation. While the data analysis uses Cresswell's analysis model, and the data validity technique uses triangulation. The results showed that the routine of ANTARA News's online media reporter NTT in producing news consisted of five stages, including preparing the agenda for coverage, coverage, news script writing, editing by the editor, and dissemination to the general public. ANTARA News NTT online media reporter interpreted his routine in producing news, including journalist rituals, part of a journalist's life, and the demands of the profession.